Phytochemical And Antibacterial Activityof Leave Extracts Of Guiera Senegalensis Lam On Selected Species Of Gram Positive And Gram Negative Bacteria - Mamman, IA; Isa, MA (International Journal of Environment, 2013)
The aim of this study was to determine the preliminary phytochemical component and antibacterial activity of the leaves extract of Guiera senegalensis lam (Combretaceae) against three clinical isolates (Staphylococcus aureus, E. coli and Klebsiella species) using standard method of analysis. The test for phytochemical component revealed the presence of alkaloid, anthraquinolones, tannin and phlobatanins. The result of antibacterial activity showed that the ethanolic extract exhibit higher zone of inhibition against all the clinical isolates, with E. coli and Klebsiella species showed zone of inhibition of 35mm followed Staphylococcus aureus 30mm. Similarly, both aqueous and methanolic extract were sensitive to all the clinical isolate except Klebsiella species which showed resistance to the methanolic extract of the leaves. The results obtained in this research imply that the leaves extract of Guiera senegalensis lam could be useful in the treatment of infections caused by Staphylococcus aureus, E. coli and Klebsiella species. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 262-268 DOI: http://dx.doi.org/10.3126/ije.v2i1.9226